Crimes of the powerful : white-collar crime and beyond - Rothe, Dawn, 1961-; Kauzlarich, David (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"As politicians and the media perpetuate the stereotype of the "common criminal," crimes committed by the powerful remain for the most part invisible or are reframed as a "bad decision" or a "rare mistake." This is a topic that remains marginalized within the field of criminology and criminal justice, yet crimes of the powerful cause more harm, perpetuate more inequalities, and result in more victimization than street crimes. Crimes of the Powerful: Beyond White Collar Crime is the first textbook to bring together and show the symbiotic relationships between the related fields of state crime, white-collar crime, corporate crime, financial crime and organized crime, and environmental crime. Dawn L. Rothe and David Kauzlarich introduce the many types of crimes, their theoretical relevance, and issues surrounding regulations and social controls for crimes of the powerful. Themes covered include: media, culture, and the Hollywoodization of crimes of the powerful; theoretical understanding and the study of the crimes of the powerful; typology of crimes of the powerful with examples and case studies; victims of the crimes of the powerful; the regulation and resistance of elite crime. Fully updated and revised, the new edition includes new chapters on occupational crime, crimes against the environment, and further coverage of representations of resistance to crimes of the powerful in popular culture. An ideal introductory text for both undergraduate and postgraduate students taking modules on the crimes of the powerful, white-collar crime, state crime, and green criminology, this text includes chapter summaries, activities and discussion questions, and lists of additional resources including films, websites, regulatory agencies and additional readings"--
OCLC-licensed vendor bibliographic record.
Keywords: State crimes; Commercial crimes; SOCIAL SCIENCE / Criminology